Designing Scientific Writing Materials Using Task Based Language Teaching - Testiana Deni Wijayatiningsih; Enny Dwi Lestariningsih; Dwi Ampuni Agustina (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2018)
One of the consequences of teachers as functional positions is that teachers are required to carry out continuous professional development (PKB), so they can carry out their duties and functions professionally. Continuous professional development is the development of teacher competencies carried out in accordance with the needs, gradually, continuously to improve their professionalism; one of them is scientific publication (KTI) or academic writing. This study aims to determine the process of designing the Task Based Language Teaching method in scientific writing material and examine the learning outcomes of elementary school teachers who take tutorial courses on Scientific Work Writing Techniques based on Task Based Language Learning. The subjects of this study were students who took the eight semester of Scientific Writing Techniques course. The method of this research used the modified 4-D instructional development model of Thiagarajan, Semmel and Semmel (4-D models). The methods of collecting data used interviewing, observing, test, and filling out questionnaires. The results show that the application of the Task Based Language Teaching method is appropriate to use in classroom tutorial teaching by considering the results of validation, namely conformity to concept indicators, content feasibility indicators, presentation indicators, and competency indicators with existing RAT and SAT along with Engineering learning modules Writing Scientific Work. Furthermore, students' self-concept is good in learning the Scientific Writing Technique in the tutorial class. This means that students' self-concept had a good improvement and reached a percentage above 70%. This proves that the application of the Task Based Language Teaching method runs seamlessly and according to what is expected. All in all, the students are more enthusiastic and challenging in writing research articles.